PERKUATAN ELEMEN BALOK BETON BERTULANG MENGGUNAKAN MATERIAL CFRP : STUDI KASUS GEDUNG BANK - Yanisfa Septiarsilia; Anditya Hendra Pratama; Jaka Propika; Indra Komara; Heri Istiono; Ahmad Hernadi (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2026)
ABSTRACT: The addition of floors and changes in building function can modify the load distribution and affect the capacity of structural elements, making it necessary to evaluate the existing structure to ensure that it can safely accommodate the new loading conditions. If the capacity is insufficient, strengthening is required, one method being the use of Carbon Fiber Reinforced Polymer (CFRP). This study includes the collection of existing structural data, structural modeling using analysis software, and the application of loads based on actual building conditions. The modeling results are used to assess the beam’s capacity under the additional loads, and if it does not meet the required strength, a strengthening system using CFRP is designed. In this research, an analysis was carried out on beam component B1 As 2-3 with a span length of 4.8 meters, considering an additional dead load from screed of 27.32 kN and an additional live load of 31.93 kN due to the functional change from office space to corridor. These added loads resulted in a new ultimate moment of 642.26 kNm, while the beam’s nominal moment capacity was only 530.29 kNm, indicating a required strengthening of at least 111.97 kNm. The analysis determined that three layers of CFRP were required, and with the CFRP installation, the new nominal moment capacity increased to 766 kNm, providing a total strength improvement of 44%.Keywords: Structural Strengthening, Beam Element, CFRP, Material, Reinforced Concrete. ABSTRAK: Penambahan lantai dan perubahan fungsi bangunan dapat mengubah distribusi beban dan kapasitas elemen struktur, sehingga diperlukan evaluasi untuk memastikan kemampuan struktur eksisting menahan beban baru. Bila kapasitas tidak mencukupi, perkuatan diperlukan, salah satunya menggunakan Carbon Fiber Reinforced Polymer (CFRP). Penelitian ini mencakup pengumpulan data eksisting, pemodelan struktur dengan bantuan perangkat lunak analisis struktur, serta penerapan pembebanan sesuai kondisi aktual. Hasil pemodelan digunakan untuk menilai kapasitas balok terhadap beban tambahan, dan jika tidak memenuhi syarat kekuatan, dirancang sistem perkuatan dengan CFRP. Pada penelitian ini dilakukan analisa komponen struktur balok B1 As 2-3 dengan panjang bentang 4.8 meter dengan penambahan beban mati akibat screed sebesar 27.32 kN dan beban hidup akibat perubahan fungsi ruang kantor menjadi koridor sebesar 31.93 kN. Dari penambahan beban tersebut didapatkan momen ultimate yang baru yaitu sebesar 642.26 kNm. Sedangkan momen nominal balok tersebut hanya sebesar 530.29 kNm, sehingga dibutuhkan perkuatan setidaknya sebesar 111.97 kNm. Dari hasil analisa didapatkan jumlah layer CFRP yang dibutuhkan yaitu sebanyak 3 layer, dengan penambahan CFRP didapatkan momen nominal yang baru yaitu sebesar 766 kNm. Dengan begitu didapatkan penambahan perkuatan sebesar 44%.Kata kunci: Perkuatan Struktur, Elemen Balok, CFRP, Material, Beton Bertulang.